Tobacco use patterns and attitudes in Singapore young male adults serving military national service: a qualitative study - Mee-Lian Wong; Jeong Kyu Lee; Clive Tan; Lavinia Lin; Mervyn Lim; Seeu Kun Ong (BMJ Open, 2020)
Objectives To explore tobacco use patterns and factors influencing tobacco use in young Singaporean men serving military national service.Methods A qualitative study using in-depth telephone interviews and maximum variation sampling was conducted with 29 Singaporean men who have completed their national service in 2017–2018. Data were analysed using thematic analysis.Results More than half (51.7%) of the participants started smoking before age 18, with a mean age of smoking initiation at 16 years. At the individual level, the two main contributing factors to tobacco use were smoking as a coping mechanism, and physical or psychological addiction. Financial concern was reported as the key motivation to quit smoking. At the interpersonal level, peers and superiors played an influential role in the smoking habits of the participants. When superiors took additional measures against smoking behaviours, it contributed to their decision to smoke less. At the organisation level, some unintended consequences were reported as a result of the strict tobacco control measures implemented by the military, such as the designated smoking areas within the camps become regarded as an area for socialisation.Conclusion Informed by the Socio-Ecological Model, this study has provided insights into the multifaceted and interactive effect of individual, interpersonal and organisational factors that influence tobacco use in young men serving military national service in the Singapore and Asian context. The study insights provided an understanding of the local context before designing programmes or changing regulations to further discourage tobacco usage in the military.